TREN PENELITIAN PENDIDIKAN MATEMATIKA DI SOUTHEAST ASIAN MATHEMATICS EDUCATION JORNAL(SEAMEJ) TAHUN 2021- 2022 - Dewi, Mella Permata; Wahyuni, Annisa Tri; Putra, Aan (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2023)
The publication of mathematics education research results has increased and developed from time to time, especially in accredited national journals. This study aims to provide an overview of research trends in the field of mathematics education published in Southeast Asian Mathematics Education Journal (SEAMEJ) and identify future mathematics education research opportunities. This research is a scoping literature review using the five-stage Arksey O'Malley framework. The review was conducted on 20 articles in the field of mathematics education published in Southeast Asian Mathematics Education Jornal (SEAMEJ) in the period 2021-2022. The result of research on the topic of mathematics education research in the past were dominated by the design of learning model changing towards teaching materials used in learning. Mathematical method will also evolve over time. Mathematics education research in the past still used a lot of quantitative approaches and changed to qualitative approaches. The subjects of mathematics education research were dominated by junior high school students. It is hoped that further research can broaden the observed dimensions, for example on the topic of mathematics education research studies to be able to study ethnomathematics.